Palladium Catalysts on Alkaline-Earth Supports for Racemization and Dynamic Kinetic Resolution of Benzylic Amines - Parvulescu, Andrei N.; Jacobs, Pierre A.; De Vos, Dirk E. (Chemistry : a European journal, 2007)
Palladium catalysts on alkaline‐earth supports were studied as new heterogeneous catalysts for racemization of chiral benzylic amines such as 1‐phenylethylamine. Particularly 5 % Pd/BaSO4 and 5 % Pd/CaCO3 were able to selectively racemize amines, with minimal formation of secondary amines or hydrogenolysis to ethylbenzene. In contrast, these side reactions were pronounced on Pd/C. A reaction mechanism is proposed that is consistent with the reaction kinetics. The catalyst activity was found to depend on the number of available surface Pd atoms, determined by titration with CO. The selectivity crucially depends on the rate of condensation of the amine and the primary imine, which is highest on Pd/C. The racemization catalysts were combined in one pot with an immobilized lipase to perform dynamic kinetic resolution of chiral amines. High yields (up to 88 %) of essentially enantiopure amides were obtained in a single step. The chemo‐enzymatic catalyst system proved to be stable and could be reused without losing the initial activity. Chiral amides are formed in high yields and essentially enantiopure form in a one‐pot reaction using a combination of a heterogeneous catalyst, Pd supported on an alkaline‐earth compound, for amine racemization and an immobilized enzyme for kinetic resolution (see scheme).